MnFePSi-based magnetocaloric packed bed regenerators: Structural details probed by X-ray tomography. (16th January 2018) - Funk, Alexander; Zeilinger, Michael; Miehe, Anja; Sopu, Daniel; Eckert, Jürgen; Dötz, Florian; Waske, Anja
Graphical abstract: Highlights: Internal 3D structure of a BASF magnetocaloric heat exchanger. TC -layer identification by four different structural features. Local porosity oscillations at the TC -layers' interfaces observed. Modeling of packed spheres validates observed porosity oscillations. Abstract: Magnetic refrigeration is considered as an alternative to conventional gas-compression-expansion cooling techniques. While the physical properties of magnetocaloric materials have been studied extensively, the question of how to process and shape these materials into active magnetic regenerator (AMR) heat exchangers for application in magnetocaloric cooling devices is less explored. Packed beds made from gas atomized spherical particles offer attractive shaping options to realize an AMR. In this work, we show that X-ray computed tomography (XCT) allows for non-destructive testing of the packed bed magnetic regenerators, including 3D visualization of the internal bed structure, measurement of the particles' packing density and homogeneity, detection of defects, cracks and interfaces between the layers with different transition temperatures. In this way, XCT can help to understand structural details of fabricated magnetocaloric regenerators and their influence on the performance in a cooling device.